Patient satisfaction with intravenous regional anaesthesia or an axillary block for minor ambulatory hand surgery: A randomised controlled study. Issue 10 (October 2020) - Teunkens, An; Vermeulen, Kristien; Belmans, Ann; Degreef, Ilse; Van de Velde, Marc; Rex, Steffen
Abstract : BACKGROUND: Intravenous regional anesthesia (IVRA) and the axillary brachial plexus block are popular alternatives to general anaesthesia in ambulatory hand surgery. Although both have proven their effectiveness, patients' preferences have never been evaluated. OBJECTIVES: We investigated patient satisfaction with both techniques and hypothesised that satisfaction after IVRA is noninferior compared with axillary brachial plexus block. DESIGN: A prospective, randomised controlled trial. SETTING: Ambulatory surgical day care centre, University Hospitals of Leuven, Belgium, from September 2016 to November 2017. PATIENTS: One hundred and twenty adults undergoing minor ambulatory hand surgery were included in this study. INTERVENTION: Patients received either IVRA with 300 mg lidocaine or an axillary block with 280 mg mepivacaine. MAIN OUTCOME MEASURES: The primary endpoint was the evaluation of patient satisfaction using the 'Evaluation du Vécu de l'Anésthesie Locoregional' (EVAN-LR) questionnaire. Secondary outcomes included different procedural times, block quality, tourniquet discomfort, the incidence of block failure and postoperative nausea and vomiting (PONV), the severity of postoperative pain and the need for postoperative analgesics during the first 24 h. RESULTS: Noninferiority of IVRA was shown for the median [IQR] total score on the EVAN-LR questionnaire, IVRA-group: 92 [87 to 96] vs. axillary brachial plexus block-group: 91[87 to 97]; Hodges--Lehmann estimator (95% confidence interval (CI)] for the shift: −0.25 (−2.60 to 2.20). Induction of anaesthesia and time to discharge, requiring partial recovery of the motor block, were significantly longer in the axillary brachial plexus block group. The IVRA-group had a lower block quality, a higher incidence of tourniquet-discomfort and higher median intra-operative and postoperative pain scores on day 0; 0 [0 to 2] vs. 0 [0 to 0] and 0.8 [0 to 1.8] vs. 0 [0 to 0.25], respectively, but no increase in the need for supplementary analgesics or conversion rate to general anaesthesia. CONCLUSION: IVRA and axillary brachial plexus block result in comparably high patient satisfaction in ambulatory hand surgery. CLINICAL TRIAL REGISTRATION: EudraCT 2016-002325-11. Abstract : Supplemental Digital Content is available in the text